Black Kite Populations Are Suffering Declining Trends In Kurukshetra And Likely To Get Further Depleted: An Analysis Of Causes - Kaushik, Tirshem Kumar; Gupta, Rohtash Chand (Journal of Tropical Life Science, 2014)
Black Kite Milvus migrans was seen capturing and captivating everything nearby the offal and garbage sites in Kurukshetra environs until recent past. Today it has been observed that between 2000 and 2010, its depletion is speeding fast, although not noticed in the scientific and social world. The skies in late morning hours are empty. Garbage sites demonstrate the absence of criss-crossing flights of this Kite. The popular sites of the roosting in the shape of Peepal Ficus religiosa, Banyan Ficus benghalensis and Mango Mangifera indica trees have been cut down in the first place. In Kurukshetra, the prime reason for the depletion could be attributed to destruction of foraging grounds (Elimination of garbage dumping sites), cutting down of traditional roosting and nesting sites and construction of colonies in the nearby erstwhile agriculture fields. The contiguous agriculture fields are devoid of any traditional trees like Peepal, Mango and hence no roosting and nesting places. The soaring Kites in the high skies in the forenoon and afternoon sessions were more or less absent. So much so that huge Garbage sites at Panipat Railway compound had no Black Kites. Shockingly, it seems that like Vultures, Black Kites are on their way to elimination in Haryana.